Urinary tract infections in seniors initiated by Proteus spp. - Porada, Mateusz; Husejko, Jakub; Skierkowska, Natalia; Gajos, Małgorzata; Prylińska, Monika; Szmelcer, Beniamin; Topka, Weronika; Modrzejewski, Mateusz; Wąsicki, Mariusz; Wysocka, O.; et al. (Journal of Education, Health and Sport, 2019)
Background: Urinary tract infection is a bacterial infection of the urinary tract or kidneys. The most common affliction affects the elderly. Depending on the age, gender, and comorbidities, there are many factors that cause UTI. Urinary tract infection is a state when pathogens are found in the urinary tract. Diagnostics and treatment of UTI, despite highly developed medicine, are a problem for clinicians, because the beginning of infections are asymptomatic. In the later stages of the infection, symptoms may vary depending on the sex and age of the patient. The most common bacterium that causes UTI is Escherichia coli. However, a large number of men over 60 years of age are caused by Proteus spp. Material and Methods: In this article the most up-to-date literature from the EBSCO and Google Scholar websites has been analyzed. Keyword used: Urinary tract infections, Proteus spp, elderly people. Results: Bacteria of the genus Proteus spp are gram-negative uropathogens belonging to the Enterobacteriaceae family. They may cause different types of infections within the human body, however the most common of which is urinary tract infection (UTI). Older people are particularly exposed to urinary tract infections due to involutionary changes that begin to dominate in the human body after the age of 60, as well as many diseases and their complications that occur in this age group. In older men more often than women, the pathogen responsible for this disease is Proteus spp. (Male gender slightly over 20% of cases, female gender - about 6%). Conclusions: A relationship between urinary tract infection and the occurrence of other diseases such as diabetes, urolithiasis or obesity can be observed. The risk of infection increases also in hospitalized patients who undergo long-term instrumentation of the urinary tract. During the treatment of urinary tract infections the most important role is pharmacological treatment, i.e. antibiotics. A secondary, though stil very important role fulfills a physiotherapy. Thanks to relaxation and breathing excercises, and pelvic floor muscle training physiotherapists can significantly improve the quality of life of geriatric patients with UTI.